2022
DOI: 10.3390/plants11212855
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Approach to the Flavonoid Profile in Some Plants’ Parts of the Annona Genus

Abstract: The Annonaceae family is widely distributed in subtropical and tropical regions. Several species of this family are known for their pharmacological and beneficial properties to human health, mainly attributed to flavonoids. The objective of this work was to carry out an integrative review in order to identify the main flavonoids found in some plant parts belonging to the Annona genus: araticum tree (Annona crassiflora Mart.), graviola tree (Annona muricata), atemoya tree (Annona cherimolia Mill × Annona squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…Physicochemical aspects, such as total titratable acidity (0.51 g citric acid/100 g), pH (4.64), humidity (74.30%), and high levels of total soluble solids (13° Brix) [ 6 , 91 ], allow araticum fruit to be widely used for dessert production, such as sweets (sweet paste, fruit preserves, and milk caramel) and jams, but the fruit can also be used in the fermented milk drinks, juices, yogurt, food bars, bread, and flour ( Table 3 ).…”
Section: Applications Of Araticum Fruit In the Foods And Beverages De...mentioning
confidence: 99%
“…Physicochemical aspects, such as total titratable acidity (0.51 g citric acid/100 g), pH (4.64), humidity (74.30%), and high levels of total soluble solids (13° Brix) [ 6 , 91 ], allow araticum fruit to be widely used for dessert production, such as sweets (sweet paste, fruit preserves, and milk caramel) and jams, but the fruit can also be used in the fermented milk drinks, juices, yogurt, food bars, bread, and flour ( Table 3 ).…”
Section: Applications Of Araticum Fruit In the Foods And Beverages De...mentioning
confidence: 99%
“…The most common flavonoids found in araticum (A. crassiflora Mart.) were epicatechin, quercetin, and rutin (RAMOS et al, 2022b). Another study by Ramos et al (2022a) revealed that not only the pulp, but also the peel and seed, treated as food waste, contain compounds with noticeable biological activities, such as alkaloids and acetogenins, among other secondary metabolites.…”
Section: Faunamentioning
confidence: 99%
“…Os flavonoides mais comumente encontrados no araticum (A. crassiflora Mart.) foram epicatequina, quercetina e rutina (Ramos et al, 2022b). Outro estudo de (Ramos et al, 2022a) revelou que não só a polpa, mas também a casca e a semente, tratadas como resíduo alimentar, contêm compostos com atividades biológicas perceptíveis, como alcaloides e acetogeninas, entre outros metabólitos secundários.…”
Section: Fonte: Autores (2023)unclassified